2008
DOI: 10.1159/000123838
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Carcinogenesis

Abstract: Pancreatic cancer is an almost universally lethal disease. Research over the last two decades has shown that pancreatic cancer is fundamentally a genetic disease, caused by inherited germline and acquired somatic mutations in cancer-associated genes. Multiple alterations in genes that are important in pancreatic cancer progression have been identified, including tumor suppressor genes, oncogenes, and genome maintenance genes. Furthermore, the identification of noninvasive precursor lesions of pancreatic adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
180
0
20

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(200 citation statements)
references
References 138 publications
(146 reference statements)
0
180
0
20
Order By: Relevance
“…Chemotherapies and radiotherapies are largely ineffective, and metastatic disease frequently recurs even after surgical resection of primary lesions (2)(3)(4). Recently, a number of risk factors have been identified, including age, cigarette smoking, high dietary intake of meat and fat, low serum folate levels, obesity, long-standing diabetes mellitus, chronic pancreatitis and family history (5), but exactly how these risk factors contribute to carcinogenesis remains largely unknown. Therefore, novel strategies for the prevention of tumor progression and metastasis are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapies and radiotherapies are largely ineffective, and metastatic disease frequently recurs even after surgical resection of primary lesions (2)(3)(4). Recently, a number of risk factors have been identified, including age, cigarette smoking, high dietary intake of meat and fat, low serum folate levels, obesity, long-standing diabetes mellitus, chronic pancreatitis and family history (5), but exactly how these risk factors contribute to carcinogenesis remains largely unknown. Therefore, novel strategies for the prevention of tumor progression and metastasis are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The K-ras gene point mutation generally occurs in codons 12, 13 and 61, with a highest mutation rate at codon 12. Research has shown that the K-ras gene mutation rate in pancreatic cancer is approximately 90% (19). It has been found that a point mutation of codon 12 of the K-ras gene is an early event in pancreatic cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note in the 43-year-old patient's tumor was the absence of the oncogenic K-RAS mutations, especially as mutations that constitutively activate K-RAS signaling have been identified in more than 95% of sporadic pancreatic adenocarcinoma. 4 Taken together, the clinicopathologic findings and molecular features of pancreatic adenocarcinoma in these patients with WS raise the possibility of a causal relationship between development of pancreatic adenocarcinoma and their underlying WS.…”
Section: Introductionmentioning
confidence: 87%
“…4 Pancreatic intra-epithelial neoplasia (PanIN) initially exhibit genomic instability and senescence-associated telomere shortening. 5,6 Progression of PanIN to invasive adenocarcinoma is accompanied by aberrant activation of Hedgehog signaling, oncogenic K-RAS mutations signs of WS, including premature graying of hair, diffuse muscular and dermal atrophy, voice changes and classic "bird-like facies" (Fig.…”
Section: Introductionmentioning
confidence: 99%